E-Governance, Metropolitan Governance and Development Programming. The Case of the Thessaloniki Metropolitan Area - Dimitris Foutakis; Elisavet Thoidou (European Regional Science Association (ERSA), 2006)
e-Governance has recently emerged as a new field of interest for both researchers and public policy makers. This has to do in the first instance with the rise of information and communication technologies and with the strategy for promotion of the information society. It also reflects growing interest in the capacity of various forms of governance to manage complex development issues and facilitate decision-making in the era of globalization. The potential of e-Governance extends from improvement of public services at the various levels of administration to empowerment of community engagement within decision-making processes. e-Governance is also of manifest relevance to questions such as the digital divide and democratic participation. Metropolitan areas in particular are considered to be at the centre of the developmental process. They thus become the appropriate spatial level for the implementation of development programmes aimed at enhancement of competitiveness and employment. New forms of multilevel metropolitan governance emerge, in response to the economic and institutional transformations occurring in them. e-Governance represents a new challenge for metropolitan governance and in particular for development programming. In the context of the EU structural regional policy, development programming in Greece identifies the development of metropolitan areas as one of its main policy objectives. e-Governance is in any case a basic component of the Information Society strategy. This paper examines the implementation of e-Governance in the Thessaloniki metropolitan area, in the specific context of development programming. From this starting point, lessons are drawn for the necessity of e-Governance as an element of metropolitan governance.
Keywords: 330